The Role of the Arab-Islamic World in the Rise of the West Implications for Contemporary Trans-Cultural Relations - Al-Rodhan, Nayef R.F.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2012)
This book takes a fascinating look at the role of the Arab-Islamic world in the rise of the West. It examines the cultural transmission of ideas and institutions in a number of key areas, including science, philosophy, humanism, law, finance, commerce, as well as the Arab-Islamic world's overall impact on the Reformation and the Renaissance.
Keywords: International relations; International organization; Middle East—Politics and government; Political sociology; Political science; Globalization; International Relations; International Organization; Middle Eastern Politics; Political Sociology; Political Science; Globalization